2017
DOI: 10.1111/ina.12385
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of inflammatory and allergic responses to common mold species: Results from in vitro experiments, from a mouse model of asthma, and from a group of asthmatic patients

Abstract: Most studies on molds focus on Alternaria alternata and Aspergillus fumigatus. Here, we report on inflammatory and allergenic properties of more typical indoor species Aspergillus versicolor, P. chrysogenum, C. cladosporioïdes, and C. sphaerospermum that were compared to A. alternata and A. fumigatus. In a mouse model, after intranasal instillation, A. alternaria, A. versicolor, and C. sphaerospermum induced the early recruitment of neutrophils and the strong expression of inflammatory markers in the bronchoal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 59 publications
2
14
0
Order By: Relevance
“…Previous studies have reported similar differences between the two Aspergillus spp. in mouse dendritic cells . In accordance, no production of inflammatory mediators was induced by A versicolor in mouse RAW264.7, human 28SC macrophages, or A549 lung epithelial cell lines …”
Section: Characterization and Pro‐inflammatory Potential Of Mold Partsupporting
confidence: 71%
See 1 more Smart Citation
“…Previous studies have reported similar differences between the two Aspergillus spp. in mouse dendritic cells . In accordance, no production of inflammatory mediators was induced by A versicolor in mouse RAW264.7, human 28SC macrophages, or A549 lung epithelial cell lines …”
Section: Characterization and Pro‐inflammatory Potential Of Mold Partsupporting
confidence: 71%
“…Chronic inflammation is often found to be a key factor in mold-induced pulmonary diseases (Figure 1). There is a positive association between mold exposure and elevated levels of pro-inflammatory markers in the airways, [102][103][104] which are linked to several respiratory diseases.…”
Section: Role Of Inflammation In Disease Linked To Mold Exposurementioning
confidence: 99%
“…Morphological diversity of fungal particles (spherical, oblong, or fiber‐like in shape) may influence the particles aerodynamic deposition patterns in the human respiratory tract upon inhalation, and the type of immune reactions induced through cytokines, chemokines from involved immune cells dependent on the deposition sites in the airways . Species diversity is also of great importance as some common indoor fungi induce particularly allergenic responses versus others that induce non‐allergic inflammatory reactions . Therefore, we may get new insights in the role played by fungi in respiratory morbidity when we base our characterization on a holistic approach.…”
Section: Discussionmentioning
confidence: 99%
“…When inhaled, they may germinate and form hyphae [10]. While A. fumigatus is pathogenic [11,12,13], P. chrysogenum is rarely responsible for invasive disease [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…However, the impact of various mold species with regard to respiratory diseases associated with inflammatory effects has not been fully elucidated. Notably, the relative levels of A. fumigatus in indoor air are low compared to P. chrysogenum [24] which is highly predominant in indoor air [14,15]. Pro-inflammatory responses are central key elements for reducing the chances of infection due to exposure to bacteria as well as mold [10].…”
Section: Introductionmentioning
confidence: 99%